2021
DOI: 10.1038/s41598-021-94024-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of solderable intense pulsed light sintered hybrid copper for flexible conductive electrodes

Abstract: Additively printed circuits provide advantages in reduced waste, rapid prototyping, and versatile flexible substrate choices relative to conventional circuit printing. Copper (Cu) based inks along with intense pulsed light (IPL) sintering can be used in additive circuit printing. However, IPL sintered Cu typically suffer from poor solderability due to high roughness and porosity. To address this, hybrid Cu ink which consists of Cu precursor/nanoparticle was formulated to seed Cu species and fill voids in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…When the same region is compared between the g-EBL master and the nickel mold, a remarkably significant decrease in roughness can be seen as a result of using of nickel electroplating to fabricate the mold. This process is known to decrease surface roughness in a process-dependent manner . The surface smoothening can also be optically observed when comparing the inflow region in the g-EBL master structure (Figure b) and nickel mold (Figure c).…”
Section: Resultsmentioning
confidence: 81%
“…When the same region is compared between the g-EBL master and the nickel mold, a remarkably significant decrease in roughness can be seen as a result of using of nickel electroplating to fabricate the mold. This process is known to decrease surface roughness in a process-dependent manner . The surface smoothening can also be optically observed when comparing the inflow region in the g-EBL master structure (Figure b) and nickel mold (Figure c).…”
Section: Resultsmentioning
confidence: 81%
“…The hydroxyl group contained in EC is oxidized in the IPL sintering process and acts as a reducing agent for copper ions. 22,33 It was confirmed that the prepared copper ion ink for screen printing has a very simple composition, can be dried quickly at a low temperature after printing, and can be easily sintered with IPL irradiation. As a result, a copper pattern with a low resistivity of 5 μΩ•cm could be formed on a poly(ethylene terephthalate) (PET) substrate by screen printing using the transparent copper ion ink and sintering as short as 20 ms using IPL.…”
Section: ■ Introductionmentioning
confidence: 91%
“…To solve this problem, copper ion inks that do not use nanoparticles are actively being studied. The predominantly studied copper precursor is copper formate, and inks formulated with it have the advantage of being able to decompose cleanly at low temperatures without leaving any organic residues. As other copper precursors, copper acetate, copper hydroxide, and copper nitrate were also studied. These inks are mainly formulated with alcohol or polyol solvents and many complexing agents such as amines or acids.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature on textile electrophoretic deposition focuses on the deposition of conductive polymers, such as polyesters or metal oxides, on fabrics made of conducting polymers. This can find applications in different kinds of sensors, flexible and smart textiles, or flexible supercapacitors [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%